Quentin Tarantino : Shooting From the Hip - Clarkson, Wensley (London Piatkus, 1995)
Quentin Tarantino is a film director whose movies contain a stark violence and black humour that have turned him into a major influence for millions of movie fans. This is a biography of the youth-culture hero charting his rise from poverty to superstardom and exploring his films.
Include Index and Illustration
Keywords: Motion picture producers and directors -- United States -- Tarantino, Quentin